The Internal Quality Assurance System in the Robotics Extracurricular Program at SD Islam Al Ishlah Bukittinggi: A Case Study of Quality Assurance Implementation in Elementary Education - Razy, Fakhrur (Istiqra: jurnal hasil penelitian, 2026)
Implementation of the Internal Quality Assurance System (SPMI) in the robotics extracurricular program at SD Islam Al Ishlah Bukittinggi and identifying differences in service quality based on the PPEPP cycle. The study employed a case study approach using descriptive qualitative methods. Data were collected through interviews, document analysis, and activity documentation. The research results indicate that the standard-setting stage has been implemented effectively throughthe availability of a vision, mission, work plan, activity schedule, and robotics curriculum. In the standard-compliance stage, limitations were still identified regarding facilities, robotics equipment, and service access for students. Program evaluations have been conducted routinely, but documentation of follow-up actions based on evaluation results has not yet been systematically organized. Furthermore, robotics activities have a positive impact on students’ creativity, problem-solving skills, and the development of religious character through the integration of Islamic values into the learning process.